VOICE ASSISTANT – AN ARTIFICIAL INTELLIGENCE SPEECH RECOGNITION MODULE THAT TRAINS THE MACHINE TO PERFORM TASKS USING SPEECH RECOGNITION - 6138 – Cadet C Vishal (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
In the technological advancement, Computers are playing major role. The field is expanding exponentially. Artificial intelligence is the one of the widespread branch of computer science deals with building intelligent systems. AI is a bigger concept in Computer Science. It has various subsets, some of the notable subsets are Machine Learning, Deep learning, Robotics, Natural processing, Expert Systems, Speech Recognition and Machine Vision. The speech recognition is the one of the concept of Artificial Intelligence. This manuscript addresses on training the machine to accept the commands through speech. System accepts vocal instructions and performs the functions.